First-principle study of the effects of Ni doping and point vacancy on the magnetic and absorption spectrum and itinerant electron properties of ZnO. (1st September 2022) - Hou, Qingyu; Wang, Zhichao
Abstract: At present, determining which system contains the characteristics of itinerant electrons is unclear by considering the coexistence of Ni doping and O vacancies or Zn vacancies in the ZnO system. The effects of Ni doping and point vacancy on the magnetic and absorption spectra and itinerant electronic properties of ZnO were studied by using first principles. Results show that the binding energy of Zn30 NiO32 and Zn31 NiO31 systems are large, and the systems are stable. The Zn30 NiO32 system containing the O 1− -2 p state has the characteristics of itinerant electrons. The Zn31 NiO31 system has no characteristics of itinerant electrons. The Zn31 NiO31 system has room temperature ferromagnetism. The more the oxygen vacancy and the increase in Ni atom doping ratio, the higher the increase in the total magnetic moment of the doped system. This condition is consistent with bound magnetopolaron theory. Highlights: The Zn30 NiO32 system containing the O 1− -2 p state has the characteristics of itinerant electrons. The Zn31 NiO31 system has no characteristics of itinerant electrons. The Zn31 NiO31 system has room temperature ferromagnetism.